Discourse-Pragmatic and Processing-Related Motivators of the ordering of Reason Clauses in an Academic Corpus - Rezaee, Abbas A.; Nemati, Majid; Golparvar, Seyyed Ehsan (Research in Language, 2018)
The present research is aimed at examining the relative importance of the competing motivators of the sequencing of reason clauses in a corpus of research articles of applied linguistics. All the finite reason clauses accompanied by their main clauses in this corpus were collected. Random forest of conditional inference trees is the statistical modelling in this study. The findings showed that sentence-final reason clauses outnumber sentenceinitial ones. Moreover, subordinator choice and bridging, which are discourse-pragmatic constraints on clause positioning, emerged as the two more powerful predictors of the ordering of reason clauses in this corpus. Furthermore, the complexity of the clause turned out to be a stronger processing related predictor than the length of the clause.